The emergence of ethics in the philosophical education of Chemistry teachers: a curricular analysis of Pre-service teacher education in the State of Paraná (Práxis Educativa, 2023)
In this article, a study on the Philosophical Education of Chemistry teachers in the State of Paraná, Brazil, is presented. The research is based on the Philosophy of Science Education, which articulates Philosophy, Philosophy of Education and Philosophy of Science. The curricular components of courses with a Chemistry teaching certification of Federal Universities and Institutes and State Universities are analyzed. Prompted by the question: What philosophical education is shown in the education of Chemistry teachers in the State of Paraná?, a qualitative and bibliographical research in the syllabus of the Pre-service teacher education courses was carried out. The emergence of ethics in the philosophical education of Chemistry teachers emerged as one of the final categories. It was identified that ethics is linked to Philosophy and Philosophy of Science, involving ethical problems and professional ethics in Chemistry. In Philosophy of Education, ethics is shown in social relationships, citizenship and educational and professional relationships.Keywords: Chemistry Education. Ethics. Teacher education.